At-Tarbiyyah Al-Usriyyah Al-Mustanbithah Fi Da’wah Ibrâhîm ila Abîhi Azar - Ahda Sabiela (Universitas Darussalam Gontor, 2018)
This paper aims to describe the approach of Prophet Ibrahim to his father Azar when conveying the religion of tauhid. Ibrahim tried to convey dakwah to his father in a gentle way of using subtle language and polite manners. In addition, it conveys a pattern of logical debates in divine dialogues concerning basic aqeedah in several different occasions. Dialoq is implemented without having to humiliate, berate or feel superior. To bring his father and his people to the truth way, Ibrahim have to face a very long and tiring journey, from this lesson, we learn about the pattern of education conducted by Ibrahim in preaching his father and his people, so the truth can be up to the way of tenderness.